2023
DOI: 10.1088/1755-1315/1217/1/012026
|View full text |Cite
|
Sign up to set email alerts
|

Low Carbon City (LCC) Governance through Administrative and Operational Approaches by Malaysian Local Government

N B Jamaluddin,
Y A Abdullah,
H Yakob
et al.

Abstract: In Malaysia, the current practice of delivering low-carbon city approaches usually is administered and managed by the planning department in each local authority. However, this current practice may also lead to the problem of unorganized institutional administration and management. Simultaneously, the Malaysian government, through Low-carbon City Master Plan, has mentioned the need for governance restructuring for low-carbon city delivery. Therefore, this paper aims to evaluate the practice of Low Carbon City … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 31 publications
(39 reference statements)
0
1
0
Order By: Relevance
“…While the policies have been recognized for their economic dividends, they also pose sustainability challenges. Recent studies have shown that congestion and environmental degradation are the main dilemmas facing Kuala Lumpur [55].…”
Section: Study Areasmentioning
confidence: 99%
“…While the policies have been recognized for their economic dividends, they also pose sustainability challenges. Recent studies have shown that congestion and environmental degradation are the main dilemmas facing Kuala Lumpur [55].…”
Section: Study Areasmentioning
confidence: 99%